(untitled) (Indian Journal of Case Reports, 2020)
Retrocaval ureter, circumcaval ureter, or most accurately pre-ureteral vena cava is a rare vascular anomaly involving the ureter. It is believed to be due to the persistence of the right subcardinal vein. As a result, the right ureter deviates medially and goes dorsal to the inferior vena cava, crossing over it and resumes its ordinary course distally, causing varying degrees of hydroureteronephrosis. We describe a case report of a middle-aged female who was a known diabetic, presented with the right flank pain and fever. On abdominal examination, she had tenderness in the right renal angle. Her laboratory investigations were normal except for elevated glucose levels. Urine analysis showed Escherichia coli infection, which was treated with antibiotics. On imaging, revealed right retrocaval ureter with Grade IV hydronephrosis. She underwent the right laparoscopic ureteroureterostomy through the transperitoneal approach. Retrocaval ureter is one of the rare causes of hydronephrosis. The treatment is a straightforward procedure, has a good outcome.